Here today, but what about tomorrow?: Increasing organizational commitment after downsizing through customer service orientation and equity - Adair Erickson, Robin; Roloff, Michael E. (International journal of organizational analysis (2005), 2008)
Purpose - The purpose of this paper is to focus on three organizational support factors that could potentially improve organizational commitment among downsizing survivors. Design/methodology/approach - Using a sample of 2,751 employees, a secondary analysis of employee survey data examined the hypotheses that customer service orientation (CSO) and equity would moderate the strength of the two-way interaction between perceived organizational support (POS) and perceived supervisor support (PSS) when predicting organizational commitment among downsizing survivors. In this way, the impact of CSO (H1) or equity (H2) would be stronger when POS and PSS were low. A third hypothesis (H3) examined whether survivors' organizational tenure was positively related to organizational commitment. Findings - H1 and H2 were partially confirmed, indicating that CSO compensated most when PSS was low and that equity compensated most when POS was low among downsizing survivors. H3 was not confirmed as no positive correlation was found between survivors' increased organizational tenure and organizational commitment. Research limitations/implications - The sample was drawn from one US organization and, because this was a secondary analysis, established scales could not be used for some constructs. Most of the variance in the exploratory factor analysis was on the first factor, POS. Practical implications - Organizations should make every attempt to maintain or increase survivors' CSO and equity in order to improve organizational commitment. In addition, organizations cannot necessarily rely on their longer-tenured employees to stay committed after a downsizing. Originality/value - The study uncovered two previously unknown findings regarding the importance of CSO and equity to the organizational commitment of survivors.